2016
DOI: 10.1001/jamaoto.2016.1110
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Patterns of Topical Intranasal Steroid Therapy for Chronic Rhinosinusitis

Abstract: Topical intranasal steroid therapy continues to be underutilized for patients with CRS. Given the negative impact of low-quality medical care, outcomes from this study indicate a need to further evaluate factors leading to the underutilization of a recommended treatment in patients with CRS to improve overall health system performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 37 publications
1
28
1
1
Order By: Relevance
“…The rhinosinusitis commissioning guidelines produced by ENT UK in conjunction with the Royal College of Surgeons of England recommend that CRS patients have received ND and INCS for 3 months before referral to secondary care, and this is derived from the European position paper of which there is a summary version for GPs. However, this low use of primary medical treatment is not unique to the UK as shown by a recent Canadian study showing the same rate of INCS uptake (20%) and with large geographical variations. Another study of 60 patients following endoscopic sinus surgery found that overall, 57.4% of patients were non‐adherent to their prescribed nasal medication regime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhinosinusitis commissioning guidelines produced by ENT UK in conjunction with the Royal College of Surgeons of England recommend that CRS patients have received ND and INCS for 3 months before referral to secondary care, and this is derived from the European position paper of which there is a summary version for GPs. However, this low use of primary medical treatment is not unique to the UK as shown by a recent Canadian study showing the same rate of INCS uptake (20%) and with large geographical variations. Another study of 60 patients following endoscopic sinus surgery found that overall, 57.4% of patients were non‐adherent to their prescribed nasal medication regime.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the wider picture, one international study demonstrated that one in three CRS patients in primary care has poorly con- showing the same rate of INCS uptake (20%) and with large geographical variations 11 . Another study of 60 patients following endoscopic sinus surgery found that overall, 57.4% of patients were non-adherent to their prescribed nasal medication regime 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of a quality metric that assesses pre‐surgical medical therapy would be to ensure that patients have tried a reasonable course of medicines that have been shown to improve patient‐centered outcomes and reduce unwarranted variation related to the under‐utilization of recommended medical therapies . In this regard topical high‐volume saline irrigations and topical intranasal corticosteroids have the highest level of available evidence, with both of these treatment courses showing an improvement in symptoms and QOL …”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is only 1 quality metric for CRS that is being actively measured and it relates to computed tomography (CT) imaging overuse . In order to facilitate appropriate QI efforts for CRS, there is a need to define and validate further quality metrics that assess key components of the CRS care cycle …”
Section: Broad Categories Of the Otolaryngology Care Cycle For Crs Wimentioning
confidence: 99%
See 1 more Smart Citation